A Quality-Driven Methodology for Information Systems Integration - Iyad Zikra; Janis Stirna; Jelena Zdravkovic (Complex Systems Informatics and Modeling Quarterly)
Information systems integration is an essential instrument for organizations to attain advantage in today’s growing and fast changing business and technology landscapes. Integration solutions generate added value by combining the functionality and services of heterogeneous and diverse systems. Existing integration environments tend to rely heavily on technical, platform-dependent skills. Consequently, the solutions that they enable are not optimally aligned with the envisioned business goals of the organization. Furthermore, the gap between the goals and the solutions complicates the task of evaluating the quality of integration solutions. To address these challenges, we propose a quality-driven, model-driven methodology for designing and developing integration solutions. The methodology spans organizational and systems design details, providing a holistic view of the integration solution and its underlying business goals. A multi-view meta-model provides the basis for the integration design. Quality factors that affect various aspects of the integration solution guide and inform the progress of the methodology. An example business case is presented to demonstrate the application of the methodology.